2015
DOI: 10.1111/andr.12076
|View full text |Cite
|
Sign up to set email alerts
|

Actin-related protein 2/3 complex-based actin polymerization is critical for male fertility

Abstract: SUMMARYThe actin-related protein 2/3 (Arp2/3) complex is critical for regulation of actin polymerization, which is associated with sperm motility and capacitation status. However, the function of the Arp2/3 complex in male fertility has not yet been fully elucidated. Therefore, this study was designed to investigate the role of the Arp2/3 complex in different processes in spermatozoa and its consequences on fertilization and early embryonic development. In this in vitro study, mouse spermatozoa were incubated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 66 publications
(103 reference statements)
0
22
0
Order By: Relevance
“…Sperm capacitation and the acrosome reaction are closely associated with actin polymerization [63]. F-actin in the actin-related pathways plays a major role in the remodeling of actin structure, the acrosome reaction, and male fertility [64]. It is possible that the significant alterations of capacitation status in our results are related to these pathways (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Sperm capacitation and the acrosome reaction are closely associated with actin polymerization [63]. F-actin in the actin-related pathways plays a major role in the remodeling of actin structure, the acrosome reaction, and male fertility [64]. It is possible that the significant alterations of capacitation status in our results are related to these pathways (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Capacitation and the acrosome reaction both involve polymerization of actin, which is located in the post‐acrosomal and equatorial regions of spermatozoa (Olson and Winfrey, ; Castellani‐Ceresa et al, ; Sánchez‐Gutiérrez et al, ; Itach et al, ; Breitbart and Finkelstein, ; Lee et al, ). Indeed, F‐actin is present in the spermatozoa of different mammalian species (Flaherty et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from different laboratories indicates that actin polymerization occurs during capacitation in several mammalian species such as boar, guinea pig, mouse, rabbit, bovine, and human sperm (Castellani-Ceresa et al 1993;Brener et al 2003;Cabello-Ag€ ueros et al 2003;Baltiérrez-Hoyos et al 2012;Romarowski et al 2015;Lee et al 2015). The increase in F-actin was observed in the sperm head as well as in the flagellum.…”
Section: Actin Polymerization During Sperm Capacitationmentioning
confidence: 95%
“…On the other hand, activation of PKC by phorbol myristate acetate enhanced PIP2 and F-actin formation mediated by PI4K activity, while the PI3K activity and intracellular PIP3 levels were reduced. Lee et al (2015), ChiqueteFelix et al (2009) In addition, it was recently reported that diacylglycerol stimulates acrosomal exocytosis by feeding into a PKC-and PLD1-dependent positive loop that continuously supplies phosphatidylinositol 4,5-bisphosphate (Lopez et al 2012). Roldan and Dawes (1993) suggested that PLD does not make a substantial contribution to the events leading to acrosomal exocytosis.…”
Section: Cross Talk Between Pka and Pkc And Regulation Of Pld1mentioning
confidence: 99%
See 1 more Smart Citation